2018
DOI: 10.1186/s12985-017-0915-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial ribonuclease binase exerts an intra-cellular anti-viral mode of action targeting viral RNAs in influenza a virus-infected MDCK-II cells

Abstract: BackgroundInfluenza is a severe contagious disease especially in children, elderly and immunocompromised patients. Beside vaccination, the discovery of new anti-viral agents represents an important strategy to encounter seasonal and pandemic influenza A virus (IAV) strains. The bacterial extra-cellular ribonuclease binase is a well-studied RNase from Bacillus pumilus. Treatment with binase was shown to improve survival of laboratory animals infected with different RNA viruses. Although binase reduced IAV titer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
(66 reference statements)
1
11
0
1
Order By: Relevance
“…Ilinskaya and coworkers have extensively explored the potential of the RNase from Bacillus pumilus , also named Binase, on influenza A virus. The authors observed a direct action on the viral mRNA in both in vitro and in vivo models [ 265 , 266 ]. Binase was also effectively tested against CoVs (MERS-CoV and the human low pathogenic CoV-229E strain)[ 267 ].…”
Section: Mechanism Of Action Of Host Defense Rnases Against Viral Infmentioning
confidence: 99%
“…Ilinskaya and coworkers have extensively explored the potential of the RNase from Bacillus pumilus , also named Binase, on influenza A virus. The authors observed a direct action on the viral mRNA in both in vitro and in vivo models [ 265 , 266 ]. Binase was also effectively tested against CoVs (MERS-CoV and the human low pathogenic CoV-229E strain)[ 267 ].…”
Section: Mechanism Of Action Of Host Defense Rnases Against Viral Infmentioning
confidence: 99%
“…The catalytic activity of RNases was measured against yeast high-polymeric and transfer RNA, and double-stranded RNA extracted from E. coli (Vector-Best, Novosibirsk, Russia) using a SmartSpec Plus Spectrophotometer (Bio-Rad, Hercules, CA, USA), as described earlier [7]. One unit was defined as the amount of enzyme that increases the extinction of acid-soluble products of RNA hydrolysis at 260 nm per min at 37 • C. The specific activity was calculated as the enzymatic activity per 1 mg of protein.…”
Section: Determination Of Rnase Activity By Acid-soluble Products Of ...mentioning
confidence: 99%
“…Catalyzing the degradation of RNA polymers, RNases indirectly participate in many cellular processes such as gene expression, cell growth and differentiation, and immune response [4][5][6]. The ability of RNases to inhibit the growth of tumor cells and the reproduction of viruses in infected cells was also shown [7,8]. The application of RNases as antitumor and antiviral agents implies their penetration into mammalian cells which contain a cytosolic RNase inhibitor (RI).…”
Section: Introductionmentioning
confidence: 99%
“…Signals from commensal bacteria can alter the threshold for immune activation in either direction, either magnifying or diminishing them, which can impact the interferon response to viral infection . Bacterial ribonucleases can be internalized into host cells to specifically degrade influenza virus RNAs, reducing both viral burden and pro‐inflammatory signaling from activation of cytosolic toll‐like receptors recognizing viral RNA. The S‐layer of Lactobacillus acidophilus prevents alphaviruses and flaviviruses from interacting with dendritic cells, key cells for initiation of adaptive immune responses.…”
Section: Immune Recognition Of Bacterial–viral Complexesmentioning
confidence: 99%